If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x+2)(x-5)=(x+3)(x-4)
We move all terms to the left:
(x+2)(x-5)-((x+3)(x-4))=0
We multiply parentheses ..
(+x^2-5x+2x-10)-((x+3)(x-4))=0
We calculate terms in parentheses: -((x+3)(x-4)), so:We get rid of parentheses
(x+3)(x-4)
We multiply parentheses ..
(+x^2-4x+3x-12)
We get rid of parentheses
x^2-4x+3x-12
We add all the numbers together, and all the variables
x^2-1x-12
Back to the equation:
-(x^2-1x-12)
x^2-x^2-5x+2x+1x-10+12=0
We add all the numbers together, and all the variables
-2x+2=0
We move all terms containing x to the left, all other terms to the right
-2x=-2
x=-2/-2
x=1
| 23y=4y-1 | | 4(x-1)=-3(x+2) | | 7x2−28=0 | | 5x+100=3x | | 4(x-4)=60 | | -2x+32=6x | | 3(x+2)=(10-x)+11 | | 3÷3y=4y-1 | | 3÷3y=4y | | 2/7z+18=8-3/7 | | 1.9x+4.8x=18 | | 9-2p=6 | | 7,8-0,15(0,4x-8)=0,5x+4,52 | | 3.12.25=0.5q+3.75 | | 3x+9=-2x+4 | | -2x+-10=6x-42 | | 4x^2-5=2x^2+13 | | |2x-1|+5=27 | | 2÷3y=4y-1 | | 21=x/6+3 | | z/3-2=11 | | x/4=7+3 | | 13y=-4y+306 | | 8.6x-1.9=116.96 | | 4(x+2)=3x+8-2x+9 | | -3w2=84 | | 9u2=-27 | | -9v2=45 | | 2x+7x+4=5(4-9x) | | 2x7x+4=5(49x) | | 3x-10=2(4x5) | | y-9.4=3.1 |